Sweet sorrow - Nicholls, David, 1966- (Mariner Books/Houghton Mifflin Harcourt, 2020)
"From the best-selling author of One Day comes a bittersweet and brilliantly funny coming-of-age tale about the heart-stopping thrill of first love-and how just one summer can forever change a life"--